Explaining Gender in Moderating the Effect of Competency, Work Discipline and Job Satisfaction on Lecturer Performance - Wulandari, Aeni Fauziyah; Winarno, Alex; Luturlean, Bachruddin Saleh; Nur, Farihin (JURNAL AL-TANZIM, 2024)
Every educational institution certainly wants qualified teaching staff or lecturers to carry out the tri-dharma of higher education, which is an obligation for lecturers. This study aimed to determine the effect of competence, work discipline and job satisfaction on lecturer performance with gender as a moderating variable. This study used a quantitative approach with a descriptive causal research type. The population of this study consisted of lecturers of IAIN Sheikh Nurjati Cirebon, which amounted to 256 lecturers. The sample of this study was 156 lecturers. This research data collection instrument used a questionnaire of 58 statement items to measure competence, work discipline, job satisfaction and employee performance—data analysis of this study using moderated linear regression analysis with the help of the SPSS 26 program. Hasil penelitian ini menunjukkan bahwa secara parsial kompetensi, disiplin kerja dan kepuasan kerja berpengaruh signifikan terhadap kinerja pegawai. Gender memoderasi pengaruh kompetensi, disiplin kerja dan kepuasan kerja terhadap kinerja pegawai. Dengan demikian kompetensi, disiplin kerja dan kepuasan kerja menjadi pendukung bagi pegawai memiliki kinerja yang baik.